Regional development-core-periphery relations: The Greek case - Evangelinides, Mary (The Greek Review of Social Research, 1975)
An attempt was made in this paper to demonstrate the process by which regional polarization and development occur in industrializing countries. The case of Greece was presented and analyzed as an example of highly polarized regional development. In Greece the polarization process actually started in the 1830s with the emergence of the new modern Greek nation-state. It was the social change and «institutional » innovations injected into the system that transformed the «traditional» socio-economic spatial structure of the country by attracting innovative personalities; the country’s élites; and consequently all economic activities; science; education; and culture into the enclave of accelerated change, the new capital Athens, which later became the core region while the rest of the country was left in a backwater. The core region started organizing the periphery into dependency by the gradual neutralization and co-option of the periphery’s élites; by the creation of an adaptive system characterized by authority-dependency relations; and by the penetration and transformation of the periphery’s social values and institutions in the direction of greater acceptance and conformity with its own value system. The polarization process that started in the 1830s was later reinforced by the «technical» and «economic » innovations introduced in the 1950s into the system. The industrialization of the country was once again focused around the core region, Athens. But due to fundamental structural weaknesses in the country’s economy, the so-called economic «miracle» of the core region was not based on modern dynamic industry and productive investment but rather on the «spread effects» of invisible receipts which in turn stimulated consumption and construction in the core region. At the same time the periphery sank deeper and deeper in backwater and stagnation and never participated in the core region’s «miracle.» It is believed that the above process of regional polarization and development is characteristic of most industrializing countries where core-periphery relations are still predominant influences.